THE EFFECT OF CONSUMING XYLITOL-CONTAINING CHEWING GUM ON PLAQUE INDEX IN FIFTH GRADE CHILDREN SDN 71 MIBO KOTA BANDA ACEH - Nailis; Reca (Journal Dental Health, 2022)
Dental plaque is a soft deposit consisting of a collection of various kinds of microorganisms, and is a major cause of caries and periodontal disease. One way to control plaque is by chewing xylitol gum which has been proven to be quite effective in cleaning teeth from plaque, increasing salivary pH, and stimulating saliva production. Xylitol is also able to reduce the synthesis of extracellular polysaccharides that can lead to the attachment of plaque bacteria. The purpose of this study was to determine the effect of consuming chewing gum containing xylitol on the plaque index in class V Sdn 71 Mibo children in Banda Aceh City. This research method is a quasi-experimental (quasi-experimental) method using a one-group pretest-posttest design. The sampling technique is the total population, which is 33 students. This study was conducted on February 15, 2022. The data analysis in this study is quantitative data using a parametric statistical test Paired Sample T-test. The results showed that there was a significant difference between before and after chewing gum containing xylitol on plaque index scores in graders. V SDN 71 Mibo Banda Aceh City p=0.001. It can be concluded that there is an effect of consuming chewing gum containing xylitol on plaque index in fifth graders at SDN 71 Mibo, Banda Aceh City. It is recommended to all students of SDN 71 Mibo Banda Aceh City to maintain and maintain dental and oral health, namely by brushing teeth 2 times a day, in the morning after breakfast and at night before going to bed.